Aborto en adolescente: experiencia en el Hospital Nacional Cayetano Heredia - Acho, Segundo (2005)
OBJECTIVE: To determine the incidence, socio demographic characteristics and complications of abortion in adolescents. MATERIAL AND METHODS: Descriptive, retrospective, type series of cases study, done at the Cayetano Heredia National Hospital between years 2000 and 2003. RESULTS: From 2222 abortions, 325 ocurred in adolescents with incidence 14,7% largest age group was 17 to 19 years (73,6%); 59,4% had less than 12 weeks of gestation. Most frequent diagnosis was incomplete abortion (67,1%), 12,8% admitted abortion manuevers and 9,4% had a previous pregnancy. The most frequent complications on admission were anemia in 54,1% and urinary tract infection in 19,4%. CONCLUSION: Abortion in adolescents ocurred in late adolescence and the most frequent complication was acute anemia.